DILEMA EKSISTENSI DAN KESEPIAN DI ERA KONEKTIVITAS: STUDI KASUS FENOMENA DOOMSCROLLING DAN IMPLIKASINYA TERHADAP MANAJEMEN KEMAHASISWAAN DI PSDKU PNP SOLOK SELATAN - Aldi Fradana; Miftahul Hasanah; Widya Febriani; Edwar Rosman (STKIP Pesisir Selatan, 2026)
Compulsively and repeatedly scrolling through negative online news, a habit now widely known as doomscrolling, has grown into an existential problem for today's student generation living amid constant digital connectivity. This article explores the existential dilemma and loneliness felt by students at PSDKU PNP Solok Selatan as a result of this scrolling habit, and draws out what the findings mean for how student affairs should be managed. A descriptive qualitative case-study design was applied, with data gathered through in-depth interviews, direct observation, and documentation studies involving twenty currently enrolled student informants. The results show that doomscrolling deepens existential loneliness, lowers academic motivation, and produces what can be called a connectivity paradox: the more students engage with social media, the weaker the quality of their meaningful social interaction becomes. These results point to the need for an integrated overhaul of student affairs management, covering emotional digital-literacy programs, campus-based existential counseling, and digital well-being policy. Both practical and theoretical implications are discussed through the lens of existentialist philosophy and contemporary digital psychology